Development of Single Phase Induction Motor Adjustable Speed Control Using M68HC11E9 Micro controller - Hussien, Hamad Saad (2004)
Variable speed control of a single-phase induction motor could be obtained through voltage control method using semiconductor power devices. These methods suffer from the large harmonics that result from the switching operation. Besides that it has a limited speed control range. Pulse Width Modulation (PWM) technique is considered as one solution for harmonic reduction and increasing the motor efficiency. The advances in domestic and commercial applications in modern life raised the urgent needs to use low power single-phase induction motor. As a consequence, the single-phase induction motor has become the most widely used type of low power ac motors for those applications where regulating speed is of essence and three- phase power source are not available. This work investigates the performance of a closed-loop adjustable speed drive for single-phase induction motor using voltage amplitude control. A microcontroller M68HCl lE-9 has been used to implement such techniques. The microcontroller senses the speed's feedback signal and consequently provides the (PWM) signal that sets the gate voltage of the chopper, which in turn provides the required voltage for the desired speed. A Buck type chopper has been used to control the input voltage of a fully controlled single phase Isolated Gate Bipolar Transistor (IGBT) bridge inverter. The proposed drive system is simulated using Matlab / Simulink, its results were compared with the hardware experimental results. The simulation and laboratory results proved that the drive system could be used for the speed control of a singlephase induction motor with wide speed range.